Safety and Efficacy of Surgical Resection of Unruptured Low-grade Arteriovenous Malformations From the Modern Decade. Issue 6 (December 2015) - Moon, Karam; Levitt, Michael R.; Almefty, Rami O.; Nakaji, Peter; Albuquerque, Felipe C.; Zabramski, Joseph M.; Wanebo, John E.; McDougall, Cameron G.; Spetzler, Robert F.
Abstract : BACKGROUND: Recent studies have questioned the utility of surgical resection of unruptured brain arteriovenous malformations (bAVMs). OBJECTIVE: We performed an assessment of outcomes and complications of surgical resection of low-grade bAVMs (Spetzler-Martin grade I or II) at a single high-volume neurosurgical center. METHODS: We reviewed all unruptured low-grade bAVMs treated with surgery (with or without preoperative embolization) between January 2004 and January 2014. Stroke rate, mortality, and clinical and radiographic outcomes were examined. RESULTS: Of 95 patients treated surgically, 85 (25 grade I, 60 grade II) met inclusion criteria, and all achieved radiographic cure postoperatively. Ten patients (11.8%) were lost to follow-up; the mean follow-up of the remaining 85 was 3.3 years. Three patients (3.5%) with grade II bAVMs experienced a stroke; no patients died. Although 20 patients (23.5%) had temporary postoperative neurological deficit, only 3 (3.5%) had new clinical impairment (modified Rankin Scale score ≥2) at last follow-up. Eight of the 13 patients (61.5%) with preexisting clinical impairment had improved modified Rankin Scale scores of 0 or 1; and 17 of 30 patients (56.7%) with preoperative seizures were seizure-free without antiepileptic medication postoperatively. No significant differences existed in stroke rate or clinical outcome between grades I and II patients at follow-up (Fisher exact test, P = .55 and P > .99, respectively). CONCLUSION: Surgical resection of low-grade unruptured bAVMs is safe, with a high rate of improvement in functional status and seizure reduction. Although transient postoperative neurological deficit was observed in some patients, permanent treatment-related neurological morbidity was rare. ABBREVIATIONS: ARUBA, A Randomized Trial of Unruptured Brain Arteriovenous Malformations bAVM, brain arteriovenous malformation mRS, modified Rankin Scale